Problems Concerning Higher Efficiency in Teaching History of Belarus at High School - A. V. Bratochkin (Наука и техника)
History is a proper subject for realization of ideas of civil education which promotes to formation of more active civil position. On the basis of the experience accumulated in the process of history teaching the author of the paper points out several key problems which are to be given a special attention: periodization of the Belarussian history, genesis of a state, society, a family and a person.